2021
DOI: 10.32604/or.2022.03570
|View full text |Cite
|
Sign up to set email alerts
|

Computational docking and in vitro analysis identifies novel arylidene analogue FPMXY-14 against renal cancer cells by attenuating Akt

Abstract: Targeted therapies are gaining global attention to tackle Renal Cancer (RC). This study aims to screen FPMXY-14 (novel arylidene analogue) for Akt inhibition by computational and in vitro methods. FPMXY-14 was subjected to proton NMR analysis and Mass spectrum analysis. Vero, HEK-293, Caki-1, and A498 cell lines were used. Akt enzyme inhibition was studied with the fluorescent-based kit assay. Modeller 9.19, Schrodinger 2018-1, LigPrep module, and Glide docking were used in computational analysis. The nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Consistent with our pan-cancer analysis, our previous studies [8,27] found that P4HB expression was higher in tumor samples than in normal samples and P4HB downregulation could significantly inhibit the cell proliferation of six PRAD cell lines, including LNCap, C4-2, C4-2B, PC3, DU145 and 22RV1 cells. In addition, renal cancer is also a common urinary tumor which ranks the 9th most common type of cancer in males and accounts for 4.2% of novel diagnoses [28][29][30]. Several studies used bioinformatic analysis to indicate that P4HB was significantly associated with prognosis for KIRC and KIRP patients [31][32][33][34][35][36], which was consistent with our finding in this study.…”
Section: P4hb and Urinary Tumorssupporting
confidence: 89%
“…Consistent with our pan-cancer analysis, our previous studies [8,27] found that P4HB expression was higher in tumor samples than in normal samples and P4HB downregulation could significantly inhibit the cell proliferation of six PRAD cell lines, including LNCap, C4-2, C4-2B, PC3, DU145 and 22RV1 cells. In addition, renal cancer is also a common urinary tumor which ranks the 9th most common type of cancer in males and accounts for 4.2% of novel diagnoses [28][29][30]. Several studies used bioinformatic analysis to indicate that P4HB was significantly associated with prognosis for KIRC and KIRP patients [31][32][33][34][35][36], which was consistent with our finding in this study.…”
Section: P4hb and Urinary Tumorssupporting
confidence: 89%
“…The assay was carried out as described elsewhere [21] using kit method as per the manufacturer's instructions. Brie y, HUVEC cells at a concentration of 1x10 5 were grown on the provided migration inserts until con uent.…”
Section: Tumor Cell Trans-endothelial Migration Assaymentioning
confidence: 99%